Physicochemical, microstructural, and sensory attributes of frozen buffalo loins treated with sodium tripolyphosphate and sous-vide cooking - Ahmad Luthfi Puzelan,; Nur Raudhatul Syahindah Mohd Radzi,; Ishamri Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examines the effects of sous-vide cooking with varying concentrations of sodium tripolyphosphate (STPP) on the physicochemical, microstructural, and sensory characteristics of frozen buffalo loins. Samples were prepared with 0.15% and 0.30% STPP, alongside a control group without STPP, and cooked using a two-stage sous-vide process at 45°C for 3 hr, followed by 60°C for an additional 3 h. The results demonstrated that STPP significantly influenced pH, cooking loss, water-holding capacity (WHC), colour properties, Warner-Bratzler shear force (WBSF), microstructure, and sensory characteristics. Raising STPP concentration improved WHC and lowered cooking loss. STPP generated a pH rise, which delayed the denaturation of myoglobin and resulted in the sous-vide-cooked buffalo loins having a redder appearance. Scanning electron micrograph (SEM) supported the notable increase in tenderness with STPP addition, by showing structural changes in the muscle fibres; 0.3% of STPP samples displayed noticeably looser fibres and a thinner perimysium. The 0.3% STPP samples had a higher overall acceptability, texture, juiciness, and appearance score than the other samples, as indicated by the sensory evaluation using generic descriptive analysis (GDA) and principal component analysis (PCA). Therefore, it is recommended to incorporate 0.3% STPP into the sous-vide cooking process to optimize the eating quality of the frozen buffalo loins.